Pengembangan Komik Digital sebagai Media Pembelajaran Fisika Tingkat SMP - Maulida Sapira; Syafira Setya Putri; Yosi Oktaviani; Dasmo Dasmo (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2022)
Learning media is an important component to support the learning process that can stimulate students' attention and interest in learning. Making media in the form of supplement books can be a good choice as an additional learning resource to clarify the teaching materials that have been delivered. One of the learning media used is Digital Comics media which can increase students' learning motivation to be able to understand and observe the material provided by the teacher. According to Lamb & Johnson (2009), digital comics are simple comics presented in certain electronic media. The use of visual media such as comics can be used to facilitate understanding and strengthen memory. The material used as the subject of learning is the solar system. in this material there are objects such as the sun, the planets, the orbits of the planets. The method used is the method of research and development (Research and Development). Research and Development (R&D) is research that seeks to develop certain products according to the needs of today's society. This research is limited to the Develop step, which is up to the assessment stage by experts. The research instrument used was a validation sheet and an assessment sheet for experts. Assessment of product quality using a questionnaire or questionnaire. The solar system material physics comic is presented in the form of a flipbook-based physics comic. Broadly speaking, this comic contains an explanation of the storyline, introduction of characters, a summary of the material. The quality of physics comics based on the assessment of linguists, material experts, media experts, and science teachers is very good (SB). According to the presentation of the eligibility criteria, comics were deemed worthy as supplements and learning media. This shows that the comic media can be well received by students and can be used as a medium that supports the student learning process.